Why students tend to compare themselves with each other? The role of mattering and unconditional self-acceptance - Shien-Yi Kam; Kususanto Ditto Prihadi (International Journal of Evaluation and Research in Education (IJERE), 2021)
Previous studies suggested that university students who are not able to accept themselves tend to develop negative tendency to compare themselves with each other. This study aimed to investigate the role of unconditional self-acceptance (USA) in explaining the association between mattering and social comparison among Malaysian undergraduate students. Three hundred and seventy undergraduate students were recruited and asked to complete an online version of Unconditional Self-Acceptance questionnaire, Iowa-Netherlands Comparison Orientation Measure and University Mattering Scale. Data analysis was conducted by employing Bootstrap Method with 95% confidence interval and 5000 sampling. The result showed that USA partially mediated the relationship between mattering and social comparison. Mattering and USA were identified as robust protective factors of social comparison among university students.